2021
DOI: 10.3390/ijms23010195
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Insulin Resistance, Dyslipidemia and Serum Metabolome in iNOS Knockout Mice following Treatment with Nitrite, Metformin, Pioglitazone, and a Combination of Ampicillin and Neomycin

Abstract: Oxidative and nitrosative stress plays a pivotal role in the incidence of metabolic disorders. Studies from this lab and others in iNOS-/- mice have demonstrated occurrence of insulin resistance (IR), hyperglycemia and dyslipidemia highlighting the importance of optimal redox balance. The present study evaluates role of nitrite, L-arginine, antidiabetics (metformin, pioglitazone) and antibiotics (ampicillin-neomycin combination, metronidazole) on metabolic perturbations observed in iNOS-/- mice. The animals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…Pioglitazone is another highly effective antidiabetic agent for T2D that is widely used as an insulin sensitizer and acts by activating peroxisome proliferator-activated receptor gamma, leading to the activation of various pathways associated with glycemic homeostasis and lipid metabolism ( Ahmadian et al, 2013 ). A few experimental animal studies revealed that pioglitazone treatment slightly modified gut flora homeostasis ( Bai et al, 2016 ; Li et al, 2019 ; Aggarwal et al, 2021 ). Pioglitazone reversed the high abundance of Proteobacteria in high-fat diet (HFD)-induced obese rats ( Bai et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pioglitazone is another highly effective antidiabetic agent for T2D that is widely used as an insulin sensitizer and acts by activating peroxisome proliferator-activated receptor gamma, leading to the activation of various pathways associated with glycemic homeostasis and lipid metabolism ( Ahmadian et al, 2013 ). A few experimental animal studies revealed that pioglitazone treatment slightly modified gut flora homeostasis ( Bai et al, 2016 ; Li et al, 2019 ; Aggarwal et al, 2021 ). Pioglitazone reversed the high abundance of Proteobacteria in high-fat diet (HFD)-induced obese rats ( Bai et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these drugs have shown good vascular protection in preclinical and clinical studies. For instance, the common drugs used to treat diabetes, such as insulin and metformin, have been shown to be effective in stimulating the release of NO and maintaining vascular stability ( Tousoulis et al, 2008 ; Aggarwal et al, 2021 ). Moreover, metformin can regulate AMPK-related pathways to protect endothelial cells ( Ding et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another experimental study discovered that microbial metabolites, for example, hippurate and indole-3-ethanol, were decreased by pioglitazone intervention in iNOS knockout mice (122). These experiment research suggested that TZDs might have mild protective effects on gut microbiota, mainly focused on lipid and carbohydrate metabolism and inflammation.…”
Section: Thiazolidinedione Insulin Sensitizersmentioning
confidence: 99%
“…The expression of PPAR-γ is abundant in the intestinal tract; thus, it is possible that PPAR-γ agonists straightly impact on gut microbiome homeostasis to improve energy metabolism ( 119 , 120 ). However, only a few experimental animal studies explored whether TZD treatment can modify gut microbiota homeostasis ( 119 , 121 , 122 ). In a high-fructose-fed mouse model, pioglitazone partly altered gut microbiota and relieved the intestinal inflammation and epithelial barrier impairment, such as preventing the increment of the pathogenic bacteria Deferribacteraceae ( Mucispirillum ) ( 121 ).…”
Section: The Effects Of Oral Antidiabetic Drugs On Gut Microbiota And...mentioning
confidence: 99%
See 1 more Smart Citation